2021
DOI: 10.1186/s12890-020-01374-6
|View full text |Cite
|
Sign up to set email alerts
|

The CT pulmonary vascular parameters and disease severity in COPD patients on acute exacerbation: a correlation analysis

Abstract: Background It is necessary to analyze the CT pulmonary vascular parameters and disease severity in chronic obstructive pulmonary disease (COPD) patients to provide evidence support for the management of COPD. Methods COPD patients on acute exacerbation admitted to our hospital from COPD patients from January 2019 to March 2020 was selected. The characteristics and ratio of the cross-sectional area (CSA) of small pulmonary vessels to the total area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The CSAs of the small pulmonary vessels can be evaluated quantitatively on CT to identify pulmonary vascular alterations in patients with COPD [18,25]. Several studies found the CSAs of small pulmonary vessels to be associated with symptoms, pulmonary artery pressure, pulmonary function, exercise capacity, AE of COPD, and mortality [5,26,27]. In our study, similar to other studies, N total /LSA and N < 5mm /LSA showed a distinct decrease as the GOLD grades progressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CSAs of the small pulmonary vessels can be evaluated quantitatively on CT to identify pulmonary vascular alterations in patients with COPD [18,25]. Several studies found the CSAs of small pulmonary vessels to be associated with symptoms, pulmonary artery pressure, pulmonary function, exercise capacity, AE of COPD, and mortality [5,26,27]. In our study, similar to other studies, N total /LSA and N < 5mm /LSA showed a distinct decrease as the GOLD grades progressed.…”
Section: Discussionmentioning
confidence: 99%
“…COPD have been known as a heterogeneous and complex condition with a variety of pathological and clinical compartments [3,4]. Pulmonary vascular alteration is a major pathophysiological characteristic of COPD [5]. It is estimated that 30-70% of COPD patients have some degree of pulmonary vascular abnormalities due to pulmonary hypertension [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD have been known as a heterogeneous and complex condition with a variety of pathological and clinical compartments [ 3 , 4 ]. Pulmonary vascular alteration is a major pathophysiological characteristic of COPD [ 5 ]. It is estimated that 30–70% of COPD patients have some degree of pulmonary vascular abnormalities due to pulmonary hypertension [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cross-sectional areas (CSAs) of the small pulmonary vessels, quantitatively extracted from volumetric CT, are reliable indicators of pulmonary vascular alteration [ 9 ]. CSAs are associated with symptoms, pulmonary function test (PFT), and severity of emphysema [ 5 , 8 , 9 ]. The extent of emphysema increases over time in patients with COPD [ 12 ].…”
Section: Introductionmentioning
confidence: 99%